(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2024)
In Egypt, the population’s relationship with the Nile River was very close, so much so that its fauna and flora were represented everywhere, from tombs to temples. In temples, the columns which represent, in their capitals, aquatic plants typical of the Nile valley are characteristic. Starting from the temple of Horus in Edfu, where we have the contrast between the papyrus, symbol of Upper Egypt, and the lotus, symbol of Lower Egypt, and from a description of these columns, we will be able to observe the particular importance of these two plants, both as natural remedies and as raw materials, but also as a mythological reference in relation to two famous myths, such as the birth of Horus among papyrus plants or that of Atum from a lotus flower.